Prediction of successful trial of labor after cesarean – the benefit of prior vaginal delivery. (17th August 2016) - Ashwal, Eran; Wertheimer, Avital; Aviram, Amir; Wiznitzer, Arnon; Yogev, Yariv; Hiersch, Liran
Abstract: Objective : To determine predictive factors for vaginal birth after cesarean section (VBAC). Methods : A retrospective cohort study of all women with singleton pregnancies and a prior single low transverse cesarean section (CS) who attempted vaginal delivery in a tertiary hospital (2010–2014). Pregnancy outcome of women with VBAC was compared to those who failed vaginal delivery. Sub-analysis for women with no prior vaginal deliveries was performed. Pregnancies with non-cephalic presentation, estimated fetal weight >4000 g and any contraindications for vaginal delivery were excluded. Results : Of the 40 714 deliveries, 1767 women met inclusion criteria. Among them 1563 (88.5%) had a VBAC and 204 (11.5%) failed. There was no significant difference between the groups regarding maternal age, comorbidities and pregnancy complications. Predictors for VBAC were (odds ratio, 95% confidence interval) interval from prior CS (1.13, 1.04–1.22, p =0.004), previous VBAC (2.77, 1.60–4.78, p < 0.001), prior vaginal delivery prior to the CS (3.05, 1.73–5.39, p < 0.001) and induction of labor (0.62, 0.40–0.97, p = 0.03). For women with no prior vaginal birth, only birthweight was associated with VBAC (0.99, 0.99–1.00, p = 0.02). Conclusion : While different variables may influence the rate of VBAC, the predictive ability of VBAC for women with no previous vaginal deliveries remains poor.